Analisis SWOT Obat Batuk Prospan pada PT. Soho Global Health - Hermanto, Hermanto (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2016)
This study discusses the importance of a swot analysis process that addressed the issue of the power of factors that influence the success of PT. SOHO Global Health seen from the internal factors of strength, of products containing the active ingredient herbal extract of ivy leaves, supported by many clinical studies, and a good corporate image in the market the medicines made from herbs. Internal factors drawback is the absence of packing tablets / capsules, the price premium relative and physician confidence will naturally medicines (herbal) is still weak. External factors are the chances of the market (consumers) began actively searching for safe medications are made from herbs and herbal remedies have not been many outstanding with reputable pharmacy. The external factor is the threat of an active promotional activities of competitors (competitors) and drugs made from chemicals ekpektoran already widely available in Indonesia. The results of the research process SWOT analysis in PT. SOHO Global Health explained that the product is at a stage prospan Oriented Growth Opportunities Strategy to 1.77 and power of 2:08. The figure is good enough where the company has the power so that it can take advantage of the opportunities that existed until the company can grow well and be able to market the product Prospan ekpektoran drug market in Indonesia. the conclusions obtained from this study are as follows: the validity of the test results with SPSS 16 software of all respondents who researched many as 30 of the 14 indicators revealed a 100% valid, proving that r count is greater than r table. Data obtained above Cronbach alpha of 0.80 is equal to 0, 893 then the data is said to be unreliable (good).